A hybrid model of new Keynesian Phillips Curve: An application in Indonesia - Aloysius Deno Hervino (Universitas Hayam Wuruk Perbanas, 2015)
This study attempts to prove whether inflation dynamics in Indonesia can be explained by the hybrid model of New Keynesian Phillips Curve (NKPC). Output gap variable and dummy variable are also incorporated in this study as the external shock of the increase in fuel oil prices in 2004. By using a steady state model, it can be concluded that inflation dynamics in Indonesia could be explained by the hybrid model of NKPC. The variable of forward looking has significant effect on inflation dynamics, but the variable of inflationary pressure (output gap) has no significant effect on inflation dynamics. In addition, the increase in fuel oil prices in 2004 also gives pressure on the inflation rate, but when interacting with the variable of inflation (backward and forward), it even reduces its pressure on the inflation rate.